Studi Interdisipliner Fenomena Childfree Dalam Prespektif Dakwah - Haniah, Dewi; Mutiara Savitri, Fania (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
This research has the following objectives: to describe how childfree is debated and to find out how childfree can be used as propaganda material. The type of research used in this research is library research to collect and analyze data sourced from libraries in the form of books, articles, journals, documents and other library materials that can be used as reference sources by collecting data. secondary in the form of documentation, data reduction, data presentation and drawing conclusions. The research results show that the childfree phenomenon in Indonesia is not well known and still often receives negative responses from the public, giving rise to pros and cons to this day. The results also show that 1) there is a need for da'wah material to rectify the childfree issue by giving direction to the community by delivering childfree material that is correct and easy for the public to understand. 2) It's time for preachers to return society's mafahim (understanding), maqayis (standards of thinking), and qanaat (feelings of love and hate) to Islamic mafahim, maqayis, and qanaat which are based on the material of preaching, namely aqidah, law, morals, and shariat Islam.